2017
DOI: 10.1159/000455161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Influence of Prostatic Stones

Abstract: Introduction: The study aimed to explore clinical influence of prostatic stones on lower urinary tract symptoms (LUTS), seminal plasma cytokines, and serum biomarkers. Materials and Methods: A total of 70 men aged ≤50 years with LUTS divided into 2 groups: group with stones (GSt) and group without prostatic stones (GNoSt). All subjects completed the International Prostate Symptom Score (IPSS) questionnaire and National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) scoring questionnaire. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Wei et al [21] reported that the levels of B7-H3 were significantly lower in EPS from men with CPPS compared to controls. However, the clinical application of these biomarkers is limited in the case of EPS collecting failure, which may be attributed to the prostatic ducts obstruction caused by stricture, intraprostatic calcification or even prostatic stones, as patients with prostatic stones have more severe symptoms [22]. From our perspective, PSEP can potentially be widely applied in clinical evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [21] reported that the levels of B7-H3 were significantly lower in EPS from men with CPPS compared to controls. However, the clinical application of these biomarkers is limited in the case of EPS collecting failure, which may be attributed to the prostatic ducts obstruction caused by stricture, intraprostatic calcification or even prostatic stones, as patients with prostatic stones have more severe symptoms [22]. From our perspective, PSEP can potentially be widely applied in clinical evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…As chronic prostatitis progresses, fibrotic and calcified areas are inevitably formed, which cause dysuria and reinfections. 60 62 …”
Section: Discussionmentioning
confidence: 99%
“… 11 , 58 As in other chronic inflammatory diseases, tissue damage in chronic prostatitis essentially results in fibrosis and calcifications that cause lower urinary tract symptoms (LUTS), (at times obstructive) dysuria symptoms, and frequently recurring infections. 59 62 Moreover, the presence of bacteria within prostatic calcifications has been reported; therefore, calcifications represent a permanent receptacle for bacteria and cause bacterial persistence. 63 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, men aged ≤50 years with low urinary tract symptoms and prostatic stones had significantly more severe symptoms than those without stones in association with increased seminal concentration of interleukin (IL)-1β and IL-8 [2]. …”
Section: Introductionmentioning
confidence: 99%